A dual-function active electrode for hydrogen production by water electrolysis

By using hydrothermal-reduction method to grow multivariate transition metal alloy nanowire array materials on porous foam metal substrates, the problems of insufficient catalytic activity of electrodes and scarcity of precious metals during electrolytic hydrogen production are solved, and efficient and stable electrolytic water production is achieved. Hydrogen reduces energy consumption and production costs.

CN115323396BActive Publication Date: 2025-01-03GUOKE GREEN HYDROGEN (HUZHOU) TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211054643.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2025-01-03
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

In the prior art, the metal nickel electrode used in the process of electrolyzing hydrogen production lacks catalytic activity, resulting in high energy consumption and involves toxic elements. Precious metal catalysts are scarce and costly, making it difficult to achieve large-scale application.

Method used

The hydrothermal-reduction method is used to grow multivariate transition metal alloy nanowire array materials on the porous foam metal substrate. As an electrode catalyst, it has high catalytic activity and stability, and is suitable for alkaline electrolytic water-anodic and anode reactions.

Benefits of technology

It achieves efficient and stable operation under large current conditions, reduces the power cost of electrolyzing hydrogen production, avoids the use of precious metals, and has low material production costs, making it suitable for large-scale commercial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115323396B_ABST
    Figure CN115323396B_ABST
Patent Text Reader

Abstract

The present invention provides a multi-element non-precious metal alloy nanowire array material, which is mainly aimed at the problem of excessive energy consumption caused by insufficient electrode activity in the process of hydrogen production by alkaline water electrolysis. At the same time, the use of this material can also meet the working conditions under a higher current density, and at the same time has the dual functional properties of cathode hydrogen evolution and anode oxygen evolution, further improving the assembly fault tolerance of the equipment. This material is prepared by a two-step method, does not involve precious metal elements, and greatly reduces the production cost. The prepared integral catalytic electrode achieves an improvement in the efficiency of efficient water electrolysis hydrogen production and has good stability, and has industrial application prospects and commercial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material science and technology, and specifically relates to a preparation method and application of a multi-element non-precious metal alloy nanowire array material. Background Art

[0002] Hydrogen (H2), whose heat of combustion is 283 kJ mol -1 , and the only combustion product is water, which is an ideal energy carrier. At the same time, the reduction and thermal conductivity of hydrogen make it widely needed in the fields of petrochemical metallurgy, nuclear power cooling, etc. With the rapid development of my country's industry, the demand for hydrogen is also increasing day by day. According to KPMG analysis, my country's hydrogen production in 2019 has exceeded 20 million tons. However, more than 96% of hydrogen is produced by traditional thermal catalytic methods, such as natural gas conversion, alcohol reforming, water gas conversion, etc. These production processes have extremely high energy consumption, raw materials are restricted by the supply side, and the product purity is low, accompanied by extremely high carbon dioxide emissions, which is contrary to my country's goal of energy conservation and emission reduction. Since this type of hydrogen production method involves fossil fuels and carbon emissions, the hydrogen produced is defined as gray hydrogen or blue hydrogen. Therefore, it is necessary to use clean energy such as wind, light, water, and nuclear to produce green electricity. Therefore, the preparation of green hydrogen through the green electricity-electrolysis water process can meet the "zero carbon release" ecological closed loop of the entire hydrogen energy industry. However, compared with traditional hydrogen production methods, the electrolysis of water requires a lot of electricity resources in the cathode and anode electrolysis processes, which is costly, resulting in only 4% of the industry share of hydrogen production by electrolysis of water. In order to reduce energy consumption costs, the development of low-cost, high-activity, and high-stability catalytic electrodes has great application prospects.

[0003] At present, industrial water electrolysis for hydrogen production uses a relatively mature alkaline water electrolysis system, but this technology uses nickel metal as the electrolysis electrode, which does not have catalytic activity. Therefore, water electrolysis for hydrogen production has high energy consumption, and the equipment used involves toxic elements such as vanadium, which has potential harm to the environment and human body. In order to improve the efficiency of water electrolysis for hydrogen production and reduce energy consumption, precious metals such as platinum, iridium, and ruthenium have innate catalytic activity, but their natural scarcity of precious metals hinders their large-scale application. Therefore, it is urgent to develop a non-precious metal water electrolysis active electrode material that can have catalytic activity comparable to that of precious metal materials while reducing its production and material costs.

[0004] Transition metal elements, due to their unique electronic structure and relatively abundant crustal reserves, have the potential to be used as active electrode materials. However, the transition metal element itself is not active enough, and its own electronic structure needs to be regulated and optimized. Through alloying treatment, the adsorption of active H and active O by active intermediates in the process of hydrogen and oxygen evolution can be effectively optimized, thereby promoting its activity. Furthermore, in order to be suitable for high current conditions, the nanoarray microstructure can promote the mass transfer and diffusion steps, which is the prerequisite for the electrode to work at high current. In addition, in the electrolysis of water hydrogen production equipment, it is necessary to simultaneously improve the electrode activity of the cathode and anode to avoid the short board effect. Therefore, it is particularly important to develop bifunctional catalytic materials that have both cathode hydrogen evolution and anode oxygen evolution activity. And while the bifunctional hydrogen and oxygen evolution catalytic materials play an electrochemical catalytic role at the same time, mutual matching can ensure the stability of the equipment, and the homogenization of the anode and cathode can reduce the impurity contamination of the cathode during the long-term use of the equipment. In summary, there is an urgent need to develop a non-precious metal catalytic material with the same activity as precious metal materials, which also has the dual functional activity of hydrogen evolution at the cathode and oxygen evolution at the anode, and is suitable for high current conditions and feasible large-scale commercial production. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a multi-element non-precious metal alloy nanowire array material. The method adopts a hydrothermal-reduction method to prepare an active material, which is in situ grown on a porous foam metal as a conductive substrate, and is applied to the cathode and anode catalytic reaction of hydrogen evolution in alkaline water electrolysis, and has high catalytic activity. The prepared catalytic material can ensure efficient and stable operation under high current conditions. The method is easy to operate and has a wide range of applications, and can be used for large-scale production of active catalytic electrodes.

[0006] The technical solution of the present invention is as follows:

[0007] On one hand, the present invention provides an active electrode for electrolyzing water, the electrode comprising a conductive porous foam metal substrate and an active catalytic material; the active catalytic material is a rod-shaped array structure in microscopic terms; the active catalytic material is a multi-element transition metal alloy; the active catalytic material is grown on the surface of the conductive porous foam metal substrate by a hydrothermal-reduction two-step method; the active hydrogen evolution catalytic material is combined with the conductive substrate in a chemically bonded form and has strong adhesion and stability.

[0008] The active electrode is a monolithic material grown in a self-supporting form on a conductive carrier without the need for the addition of a binder.

[0009] Based on the above technical solution, preferably, the conductive carrier is one or more of foamed metal nickel, foamed metal copper, foamed metal titanium, and foamed metal alloy.

[0010] Based on the above technical solution, preferably, the active electrode catalytic material is one or more of an alloy, an iron-based alloy, a cobalt alloy, a molybdenum alloy, a copper alloy, a chromium alloy, and a zinc alloy.

[0011] Based on the above technical solution, preferably, the active electrode catalytic material is a rod-shaped array structure or a hollow array structure.

[0012] Another aspect of the present invention provides a method for preparing the above-mentioned active electrode, wherein the electrode is prepared by a hydrothermal method, and the hydrothermal method includes one or a mixture of aqueous solvents and organic solvents.

[0013] Another aspect of the present invention provides a method for preparing the above-mentioned active electrode, wherein the electrode is prepared by a hydrothermal method, and the hydrothermal method includes one or more of normal pressure and high pressure.

[0014] Another aspect of the present invention provides a method for preparing the above-mentioned active electrode, wherein the electrode is prepared by a reduction method, and the reduction method includes one or more of heating reduction and high-temperature reduction.

[0015] Based on the above technical solution, the method comprises the following steps:

[0016] (1) Selecting porous foam metals with different parameters as electrode substrate materials;

[0017] (2) The conductive foam metal substrate is placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in sequence and ultrasonicated for 1 to 30 min, and then placed in a vacuum drying oven at 50 to 70 °C for 1 to 12 h to obtain a substrate material with a clean surface, which is then sealed and stored;

[0018] (3) dissolving the alloy catalyst material precursor salt in a solvent, and then ultrasonically dispersing the mixture for 30 to 90 minutes to obtain a hydrothermal reaction solution;

[0019] (4) placing the conductive foam substrate in a hydrothermal reaction solution to carry out a hydrothermal reaction, and the obtained material is washed by ultrasonication in ultrapure water for 1 to 30 min, and then placed in a vacuum drying oven at 50 to 70 °C for 1 to 12 h and sealed for storage;

[0020] (5) Placing the hydrothermally prepared material prepared in step (4) in a reduction furnace for reduction at a temperature of about 200-1000°C for a reduction time of 1-50 hours, and sealing and storing after cooling.

[0021] The foam metal in step (1) is at least one of foam copper, foam nickel, foam titanium, and foam alloy;

[0022] The metal foam substrate described in step (1) has a pore size of 50-700 PPI and a thickness of 1-20 mm;

[0023] The cleaning solution in step (2) is 1-5 mol·L dilute hydrochloric acid. -1 , ultrapure water resistance 18.2 MΩ·cm;

[0024] The catalyst material precursor in step (3) is at least one of ammonium fluoride, nickel nitrate, cobalt nitrate, iron nitrate, chromium nitrate, sodium molybdate, ammonium molybdate, nickel sulfate, iron sulfate, cobalt sulfate, zinc sulfate, copper sulfate, ammonia water, sodium hydroxide, sodium citrate, ammonium citrate, citric acid, urea, and thiourea;

[0025] The solvent in step (3) is at least one of water, ethanol and dimethyl sulfoxide;

[0026] The total molar concentration of the precursor contained in the electroplating solution in step (3) is 0.001~20 mol·L -1 ;

[0027] The hydrothermal reaction in step (4) is carried out in a stainless steel reactor or a quartz condensation reflux device;

[0028] The hydrothermal reaction temperature of step (4) is 80-260°C, the hydrothermal reaction time is 2-72 hours, and the hydrothermal reaction needs to be stirred by a homogeneous reactor or magnetic stirring at a stirring rate of 0-700 rpm;

[0029] The reduction process in step (5) needs to be carried out in a reducing atmosphere, wherein the reducing atmosphere is at least one of hydrogen, argon, nitrogen and helium;

[0030] In the reduction process of step (5), the heating and cooling rate is 1-15°C min -1 ;

[0031] The present invention also provides an application of the above-mentioned catalytic material, wherein the material is a non-precious metal material, and the material structure is a multi-component non-precious metal alloy array. The material can be used as an integral electrode for the bifunctional catalytic reaction of hydrogen evolution at the cathode and oxygen evolution at the anode in alkaline water electrolysis, and can still maintain high activity and stability under high current density conditions.

[0032] Based on the above technical solution, preferably, the alkaline hydrogen evolution electrolyte is one or more of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution;

[0033] Based on the above technical solution, preferably, the current density of the alkaline water electrolysis reaction is 0.001~5 A·cm -2 . Beneficial Effects

[0034] 1. The present invention utilizes the synergistic effect of multi-element alloys to adjust and optimize the catalytic activity in the process of hydrogen and oxygen evolution by electrolysis of water, and can be simultaneously applied to the cathode and anode of the hydrogen production equipment by electrolysis of water, thereby improving the electrolysis efficiency and saving the electricity cost in the hydrogen production process.

[0035] 2. The catalytic electrode provided by the present invention has a nanowire array structure, grown on a conductive foam metal substrate, and has the advantages of excellent conductivity and a large specific surface area, which is beneficial to the electron conduction and mass transfer process in the reaction.

[0036] 3. The integral electrode provided by the present invention does not require an external binder and is grown in situ on the surface of the base by a hydrothermal method to form a strong chemical bond with the base, thereby greatly improving the stability and conductivity of the catalyst on the base.

[0037] 4. The integrated catalytic electrode provided by the present invention can be applied to alkaline electrolyte systems, which can effectively avoid the corrosion of the acidic system to the hydrogen production equipment, and reduce the operational difficulty and equipment maintenance cost in the process of electrolyzing water to produce hydrogen.

[0038] 5. The catalytic material of the present invention does not use precious metal elements, has low production cost, is simple to operate, has a wide range of precursor sources, can achieve large-scale preparation, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the scanning electron microscope microstructure of Example 5;

[0040] Figure 2 This is the scanning electron microscope microstructure of Example 6;

[0041] Figure 3 The alkaline water electrolysis efficiency activity test of the electrodes of Example 5 and Comparative Examples 1 to 3 was performed, and the electrolyte was 1 M KOH. DETAILED DESCRIPTION

[0042] The whole material preparation process is described in detail below by way of examples, but the scope of the claims of the present invention is not limited by these examples. At the same time, the examples only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose. The raw materials used in the following examples are all conventional products that can be obtained commercially.

[0043] Example 1

[0044] Preparation of nickel-molybdenum alloy array catalytic electrode 1:

[0045] 1. Nickel foam of a certain size (4*2 cm 2, 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0046] 2. Dissolve 0.1 mol·L in water -1 Nickel nitrate, 0.0125 mol·L -1 Ammonium molybdate, 0.15 mol·L -1 Urea, the above clarified solution was transferred to a condensation reflux reactor, and a foamed nickel substrate was added for hydrothermal reaction at a temperature of 90 °C for 6 hours.

[0047] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 10 °C min. -1 , reaction temperature 900 ℃, reaction time 10 hours, reaction atmosphere hydrogen flow rate 20 sccm min -1 , nitrogen flow rate 80 sccm -1 , cool down and set aside.

[0048] Example 2

[0049] Preparation of nickel-molybdenum alloy array catalytic electrode 2:

[0050] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0051] 2. Dissolve 0.1 mol·L in water -1 Nickel nitrate, 0.0125 mol·L -1 Ammonium molybdate, 0.15 mol·L -1 Urea, the above clarified solution was transferred to a condensation reflux reactor, and a foamed nickel substrate was added for hydrothermal reaction at a reaction temperature of 140 °C for 20 hours.

[0052] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 500 ℃, reaction time 10 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm -1 , cool down and set aside.

[0053] Example 3

[0054] Preparation of cobalt-molybdenum alloy array catalytic electrode 1:

[0055] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0056] 2. Dissolve 0.05 mol·L in 300 ml water -1 Cobalt sulfate, 0.01 mol·L -1 Ammonium molybdate, 0.3 mol·L -1 Ammonium fluoride was added, and then ethanol was added to make the volume 450 ml. The above clear solution was transferred to a high-temperature stainless steel hydrothermal autoclave, and a foamed nickel substrate was added to carry out a hydrothermal reaction at a temperature of 160 °C for 6 hours.

[0057] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 10 °C min. -1 , reaction temperature 800 ℃, reaction time 10 hours, reaction atmosphere hydrogen flow rate 20 sccm min -1 , nitrogen flow rate 80 sccm -1 , cool down and set aside.

[0058] Example 4

[0059] Preparation of nickel-molybdenum-iron alloy array catalytic electrode 1:

[0060] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0061] 2. Dissolve 0.1 mol·L in 100 ml water -1 Nickel nitrate, 0.02 mol·L -1 Ammonium molybdate, 0.05 mol·L -1 , ferrous sulfate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 160 °C for 24 hours.

[0062] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 10 °C min. -1 , reaction temperature 800 ℃, reaction time 10 hours, reaction atmosphere hydrogen flow rate 20 sccm min -1 , nitrogen flow rate 80 sccm -1 , cool down and set aside.

[0063] Example 5

[0064] Preparation of nickel-molybdenum-iron alloy array catalytic electrode 2:

[0065] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0066] 2. Dissolve 0.05 mol·L in 100 ml water -1 Nickel nitrate, 0.01 mol·L -1 Ammonium molybdate, 0.01 mol·L -1 , ferric nitrate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210 °C for 6 hours.

[0067] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 500 ℃, reaction time 2 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm -1 , cool down and set aside.

[0068] Example 6

[0069] Preparation of nickel-molybdenum-iron alloy array catalytic electrode 3:

[0070] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0071] 2. Dissolve 0.05 mol·L in 100 ml water -1 Nickel nitrate, 0.01 mol·L -1 Ammonium molybdate, 0.01 mol·L -1 , ferric nitrate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210 °C for 24 hours.

[0072] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 900 ℃, reaction time 8 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm -1 , cool down and set aside.

[0073] Comparative Example 1

[0074] Preparation of nickel-molybdenum alloy array catalytic electrode:

[0075] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0076] 2. Dissolve 0.05 mol·L in 100 ml water -1 Nickel nitrate, 0.02 mol·L -1 Ammonium molybdate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210 °C for 6 hours.

[0077] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 500 ℃, reaction time 2 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm -1 , cool down and set aside.

[0078] Comparative Example 2

[0079] Preparation of nickel-iron alloy catalytic electrode:

[0080] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0081] 2. Dissolve 0.05 mol·L in 100 ml water -1 Nickel nitrate, 0.04 mol·L -1 Ferric nitrate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210 °C for 6 hours.

[0082] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 500 ℃, reaction time 2 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm -1 , cool down and set aside.

[0083] Comparative Example 3

[0084] Preparation of molybdenum-iron alloy catalytic electrode:

[0085] 1. Nickel foam of a certain size (4*2 cm 2 , 1 mm thick), the conductive foam metal substrate was placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water in turn for 5 min of ultrasonic treatment, and then placed in a vacuum drying oven at 70 ° C for 2 h to obtain a substrate material with a clean surface, which was sealed and stored;

[0086] 2. Dissolve 0.02 mol·L in 100 ml water -1 Ammonium molybdate, 0.04 mol·L -1 Ferric nitrate, 0.03 mol·L -1 ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210 °C for 6 hours.

[0087] 3. Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1 °C min. -1 , reaction temperature 500 ℃, reaction time 2 hours, reaction atmosphere hydrogen flow rate 5 sccm min -1 , nitrogen flow rate 45 sccm-1 , cool down and set aside.

[0088] Application Example 1

[0089] The catalytic electrodes obtained in Example 5 and Comparative Examples 1 to 3 were used to evaluate the electrochemical hydrogen evolution activity under alkaline conditions.

[0090] 1. The standard two-electrode electrochemical linear voltammetric scanning method was used for analysis. The obtained electrodes were water electrolysis hydrogen evolution cathode and oxygen cathode, the electrolyte was 1 M KOH solution, the effective electrode exposure area was 1*1 cm, the inter-electrode distance was 1 cm, the solution resistance was 1.8 Ω for compensation, and the voltammetric curve scanning rate was 5 mV s -1 , test temperature: 25 ℃;

[0091] 2. The total efficiency of water electrolysis is as follows: Figure 1 As shown: nickel-molybdenum-iron array alloy electrode (Example 5)>nickel-molybdenum array alloy electrode (Comparative Example 1)>nickel-iron alloy electrode (Comparative Example 2)=molybdenum-iron alloy electrode (Comparative Example 3);

[0092] The present invention can regulate the activity of the catalyst by adjusting the hydrothermal precursor components, concentration, reaction temperature and time, and the ternary component is superior to the binary component catalytic electrode.

Claims

1. A water electrolysis material, characterized in that: It is prepared by the following method: 1) 4×2cm 2 , 1mm thick nickel foam, the conductive foam metal substrate is placed in ultrapure water, acetone, ultrapure water, dilute hydrochloric acid, ultrapure water, anhydrous ethanol, and ultrapure water for 5 minutes, and then placed in a vacuum drying oven at 70°C for 2 hours to obtain a substrate material with a clean surface, which is sealed and stored; 2) Dissolve 0.05 mol·L in 100 ml of water -1 Nickel nitrate, 0.01 mol·L -1 Ammonium molybdate, 0.01 mol·L -1 Ferric nitrate, 0.03 mol·L -1 Ammonium citrate, transfer the above clear solution to a high-temperature stainless steel hydrothermal autoclave, add a foamed nickel substrate, and perform a hydrothermal reaction at a temperature of 210°C for 6 hours; 3) Place the electrode precursor obtained in step (2) in a reduction furnace and heat it for reduction at a heating and cooling rate of 1°C min -1 , reaction temperature 500°C, reaction time 2 hours, reaction atmosphere hydrogen flow rate 5sccm, nitrogen flow rate 45sccm, after cooling, obtain nickel-molybdenum-iron alloy array catalytic electrode; The material can be used as an integral electrode and can be simultaneously applied to the catalytic processes of hydrogen evolution at the cathode and oxygen evolution at the anode of alkaline water electrolysis.